2011
DOI: 10.1016/j.eja.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of winter wheat yield and its variability in different climates of Europe: A comparison of eight crop growth models

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
264
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(287 citation statements)
references
References 49 publications
15
264
2
6
Order By: Relevance
“…One approach with crop models has been to identify models that have similar equations for underlying processes, such as photosynthesis. In general, however, it has not been found that structural similarity leads to similarity in simulated values in crop MMEs (Palosuo et al 2011;Martre et al 2015;Li et al 2015). An alternative approach, proposed for climate models (Bishop and Abramowitz 2013), is to examine the covariance in model errors as the measure of model dependence.…”
Section: Evaluating the Degree Of Relatedness Of The Models In A Mmementioning
confidence: 99%
See 2 more Smart Citations
“…One approach with crop models has been to identify models that have similar equations for underlying processes, such as photosynthesis. In general, however, it has not been found that structural similarity leads to similarity in simulated values in crop MMEs (Palosuo et al 2011;Martre et al 2015;Li et al 2015). An alternative approach, proposed for climate models (Bishop and Abramowitz 2013), is to examine the covariance in model errors as the measure of model dependence.…”
Section: Evaluating the Degree Of Relatedness Of The Models In A Mmementioning
confidence: 99%
“…The need for quality criteria to exclude poorly performing models has been discussed (Palosuo et al 2011;Rötter et al 2012). Asseng et al (2013) removed those models with the highest and lowest 10 % of simulated values in some of their analyses, but do not discuss that choice.…”
Section: Choosing the Participants In A Multi-model Ensemble (Mme)mentioning
confidence: 99%
See 1 more Smart Citation
“…In other disciplines it is less used (Table 1). However, it has been applied for prediction in ungauged basins in hydrology (Refsgaard and Knudsen 1996) and for testing a range of crop simulation models with explicit restrictions on model calibration (Palosuo et al 2011;Rötter et al 2011). As space-time-substitutions use data from other locations or periods, any test of this projection methodology involves elements of proxy site tests.…”
Section: Validation Methodologiesmentioning
confidence: 99%
“…For crop yield modelling a relevant criterion could be the frequency of yields below a critical level that exceeds the coping range of the particular farming system (Palosuo et al 2011). Similarly, for lake modelling a relevant criterion could be the probability of exceeding a critical threshold for abundance of potentially toxic cyanobacteria.…”
Section: Performance Criteriamentioning
confidence: 99%